Wilderjevo gledališče v gledališču - Orel, Barbara (Primerjalna književnost, 2003)
Wilder's Theatre within Theatre. The drama in a dialogue with the narrative. The article discusses Thornton Wilder's theatre within theatre (in Pullman Car Hiawatha, Our Town and The Skin of Our Teeth), in which the drama is put into a dialogue with the narrative. The author subjects it to formal criticism in an attempt to step out of the traditional theatrical model of reception, while showing that the structure of theatre within theatre (or rather of a play within a play) represents a bridge between the absolute and epic dramas, between their closed and open forms.
Keywords: teatrologija; theater; gledališče; dramaturgija; drama; dramatika; gledališče v gledališču; igra v igri; terminologija; terminology